Primary cerebellar myxopapillary ependymoma: Case report - Hannah R. Riva, MPAS, PA-C; Min Wang, MD, PhD; Juan Ortega-Barnett, MD, FAANS, FACS (Interdisciplinary Neurosurgery, 2022)
Myxopapillary ependymomas are a variant of ependymoma located almost exclusively in the conus medullaris-cauda equina-filum terminale region of the spinal cord. Intracranial myxopapillary ependymomas are rare, occurring either through cerebrospinal fluid seeding from the spinal cord or as primary intracranial myxopapillary ependymoma. We present a case of a large myxopapillary ependymoma in the cerebellum of a 33-year-old male, in whom the tumor was found incidentally after presentation following trauma; however, he did endorse a history of migraines and nausea/vomiting. The tumor was stereotactically resected with gross total resection. This may represent possibly the largest intracranial primary myxopapillary ependymoma. Of note, the World Health Organization 2021 classification re-classified myxopapillary ependymoma grading from grade 1 in 2016 classification to grade 2 in 2021 classification, in light of frequent recurrences, and follow-up with surveillance is recommended.